The current situation of human resources for health in the province of Cabinda in Angola: is it a limitation to provide universal access to healthcare? - Damas Macaia; Luís Velez Lapão (BMC, 2017)
Abstract Background Angola is among sub-Saharan African countries dealing with a crisis of Human Resources for Health (HRH). The province of Cabinda, besides the efforts, still suffers from both HRH shortage and a badly distributed health workforce. In Cabinda, one can find urban concentration and rural shortages of healthcare professionals, many rural areas' healthcare facilities often secured only by basic or medium level HRH; and difficulties in developing HRH retention strategies in rural areas where most services are covered by foreign HRH. This study aims at analysing the situation of HRH in the province of Cabinda. It considers organizational issues, policies and practices resulting from the HRH strategy followed in the recent years, moreover the creation of a medical school. The context that affects the distribution of the health workforce is analysed to contribute to the development of evidence-based policies that promote a better HRH allocation in the poorest and distant villages in the province. Methods A mixed-methods study was developed, combining a quantitative and qualitative approach to analyse HRH situation in the province of Cabinda. Data was collected from key informants, selected by intentional sampling from public and private health organizations, to respond to a questionnaire and a semi-structured interview. Quantitative and qualitative data was analysed with descriptive and inferential statistics and content analysis respectively. The study was complemented by a comprehensive desk review. Results Results show a clear change in HRH data from 2011 to 2015 with significant fluctuations due to variations in retirement, migration and lack of regular public HRH recruitment tenders. HRH density is apparently better in rural when compared with urban areas. However, one should bear in mind that often HRH allocated to rural areas do not stay there, which leads to real geographical imbalances. Factors like lack of proper incentives for HRH retention and social support goes against significant HRH management efforts contributing to this result. Whereas HRH are financed by the State General Budget, the majority of health facilities are still dependent on the Provincial Health Secretariat budget. Conclusion The study provides a broader view of the current HRH situation in Cabinda Province. Geographical imbalances and other issues with impact in delivering universal access to healthcare are highlighted.